Formation of process contaminants in commercial and homemade deep-fried breadcrumbs. (February 2023) - Mesías, Marta; Holgado, Francisca; Morales, Francisco J.
Graphical abstract: Highlights: Deep-fried commercial and homemade wheat-based breadcrumbs were investigated. Breadcrumbs composition conditioned the formation of acrylamide, HMF and furfural. Fried commercial breadcrumbs showed significantly higher acrylamide content. HMF content was significantly higher in fried homemade breadcrumbs. 463 µg/kg is proposed as signal value of the acrylamide content in fried breadcrumb. Abstract: Breading is a culinary technique widespread throughout the world. Deep-frying breaded foods forms a palatable crust but also promotes the formation of compounds of toxicological relevance. The influence of the composition of breadcrumbs on the risk associated with the formation of acrylamide, hydroxymethylfurfural (HMF), and furfural was investigated in a deep-fried breadcrumb coating model. Commercial (CBC) and homemade (HBC) wheat-based breadcrumbs were characterized by the reducing sugars and the asparagine content among other parameters (moisture, pH, and CIELab color). The formation of process contaminants in fried breadcrumbs were not influenced by their initial content, but they were affected by the precursors level. The HMF content was significantly higher (1.4 times) in fried HBC (172 mg/kg) than in CBC (120 mg/kg). By contrast, the acrylamide content was 3 times higher in fried CBC (332 µg/kg) than in HBC (111 µg/kg). Multivariate analysis shows that asparagine is the limiting factor for acrylamide formation, and the reducing sugar content is the main determinant for the formation of furanic compounds. A signal value of 463 µg/kg is proposed for the acrylamide content in the coating of deep-fried breaded foods. The reducing sugars and asparagine content in breadcrumb coatings should be considered when designing breaded foods, thereby reducing the formation and consequently the dietary exposure to these potentially harmful compounds.